Exendin-4 Promotes Schwann Cell Proliferation and Migration via Activating the Jak-STAT Pathway after Peripheral Nerve Injury. (15th June 2020) - Pan, Bin; Huo, Tianqun; Hu, Youzhong; Cao, Menghan; Bu, Xiangbo; Li, Ziang; Jing, Li; Luo, Xuanxiang; Gao, Xiao; Feng, Hu; Yuan, Feng; Guo, Kaijin
Highlights: Exendin-4 intraperitoneal injection promotes peripheral nerve regeneration after injury in mice. Exendin-4 intraperitoneal injection do not change blood glucose levels in mice. Exendin-4 activates the Jak-STAT signaling pathway in Schwann cells. Exendin-4 promotes Schwann cells proliferation and migration via the Jak-STAT pathway. Abstract: Peripheral nerve injury (PNI) is a common clinical disease that causes the partial loss of segmental exercise and sensory and autonomic nervous function, placing a heavy burden on patients and their families. A previous study confirmed that exendin-4 can effectively improve nerve regeneration and functional recovery after PNI. However, the specific mechanisms by which exendin-4-mediates this repair have not been clarified. To explore the mechanism of exendin-4 in the treatment of PNI, we used microarray analysis to detect gene expression in the distal segment of the sciatic nerve after sciatic injury. Bioinformatics analyses were used to predict the roles of differentially expressed genes (DEGs) in nerve damage repair. Schwann cells (SCs) were cultured, and we verified the molecular mechanism of exendin-4 in SCs and the effect of exendin-4 on peripheral nerve regeneration through in vitro molecular biology and cell biology experiments. In vivo, exendin-4 could significantly promote peripheral nerve regeneration. A total of 180 DEGs between the exendin-4 group and the control group were detected. Bioinformatics analysis indicated that these DEGs were mainly enriched in the Jak-STAT signaling pathway. In vitro, exendin-4 could significantly promote the proliferation and migration of SCs by activating the Jak-STAT pathway, which promoted peripheral nerve regeneration. Our results indicate that exendin-4 promotes SC proliferation, migration and nerve regeneration after PNI by activating the Jak-STAT pathway. Our findings provide a basis and direction for further elucidation of the mechanisms of exendin-4 in the repair of PNI and provide a new way to treat PNI.